The resistivity piezocone for high resolution geo-environmental site investigation: A Brazilian example - Riyis, M. T.; Giacheti, H. L. [UNESP] (My University, 2013)
A suitable decision-making on managing a contaminated site characterization program is strongly dependent of the diagnosis process.A detailed diagnosis can be done based on a Conceptual Site Model (CSM) elaboration using high resolution site characterization tools. The piezocone (CPTu) test is a high resolution tool which allows attaching several specific sensors, like the resistivity probe. This hybrid device is called the resistivity piezocone (RCPTu). A simulated geo-environmental site characterization program was performed on an erosion site using different tools (direct push tools soil samplers, hollow stem auger (HSA) drilling and RCPTu tests) to develop the CSM for a site similar to the Brazilian conditions. It was observed a good agreement between the site profiles interpreted by the different methods. The resistivity sensor attached to the piezocone improved the interpretation and the decision-making process on site was significantly better for the CSM elaboration. The RCPTu test data also allowed identifying the hydrogeological heterogeneities. The present study shows that the RCPTu test is also a useful and powerful tool to development an accurate CSM in a Brazilian condition, especially in an approach that prioritizes high resolution geo-environmental investigation.